Effect of Naturopathy thorax massage on spirometric variables among healthy individuals - Nikita Sharma; Nair Dhiren Ajit
Massage therapy possesses a lengthy historical background and is extensively practiced on a global scale. Substantial research has illustrated that massage represents a secure, pragmatic, and therapeutic choice. Nevertheless, the precise physiological influence of massage on the thoracic region remains inadequately comprehended. The objective of this investigation was to evaluate the effects of a 35 min thorax massage for six successive days on spirometric variability in healthy volunteers. A total of 150 healthy adult participants, aged between 21 and 25 years and encompassing both genders, were enrolled in this examination. The intervention comprised a 35 min thoracic massage, while the control cohort partook in supine relaxation and deep inhalation for six consecutive days. The primary outcome parameters, encompassing Forced Expiratory Volume in the 1st second (FEV1), Forced Vital Capacity (FVC), and FEV1/FVC ratio (absolute value), were evaluated utilizing Clarity Spirotech (Model No CMSP-01) on the 0th and 6th days of the intervention, with subsequent follow-up assessments on the 12th and 24th days. The investigation encompassed 150 healthy individuals. In contrast to the control set, the intervention group displayed noteworthy overall enhancements in FVC (p value 0.0001), FEV (p value 0.0001), and FEV1/FVC (p value 0.0001) on the 0th, 6th, 12th, and 24th days. This research deduces that a 35 min thorax massage over six successive days amplifies spirometric parameters in healthy volunteers. Nonetheless, further large-scale randomized controlled trials are essential to validate these findings across diverse respiratory disorders.